Other bodies: Other lives; other deaths - Stratton, Jon (Borderlands, 2013)
There is no doubt that we have left the modern world. The certainties that informed modern life have been transformed – though many modern practices remain. However, when we left modernity depends on which factor, or factors, of the shift we emphasise. All the essays in this issue of borderlands acknowledge the move into a different discursive order – what Michel Foucault, in an earlier moment of his career, would have called a new episteme. Indeed, in The Order of Things Foucault notes that: ‘In fact, of all the mutations that have affected the knowledge of things and their order ... only one, that which began a century and a half ago and is now perhaps drawing to a close, has made it possible for the figure of man to appear.’ (p. 386). Perhaps wisely, Foucault did not pursue this thought.